1987
DOI: 10.1111/j.1532-5415.1987.tb04339.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum B12 Levels in a Hematologically Normal Elderly Subpopulation

Abstract: Serum Vitamin B12 levels were determined on 378 patients ranging in age from 56 to 104 years with a median age of 77 for both males and females. A radiodilution method was employed for these determinations. This screening procedure identified 26 patients with low serum B12 levels. Nineteen of these patients had no other symptoms and were hematologically normal. The B12 binding proteins, transcobalamins (TC) I, II, and III were quantitated employing QUSO and DEAE cellulose batch separations. The total number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 22 publications
(28 reference statements)
6
36
1
Order By: Relevance
“…The largest group are subjects not taking Cbl in their diets (strict vegetarians), those with Cbl malabsorption due to simple atrophic gastritis affecting at least 10% of the elderly and, in decreasing numbers, those who have undergone a gastrectomy. A reduced level of R-binder (TC-I and III) and a relatively low level of Cbl on TC-II, the significant Cbl transport protein, has been found in the elderly, although the significance of this is not clear (Marcus et al, 1987;Metz et al, 1996). These patients who do not consume enough Cbl or do not absorb it normally, have low Cbl stores but, presumably, are not, as yet, sufficiently Cbl-deficient to develop MA or neuropathy and most never do so.…”
Section: The Blood and Marrowmentioning
confidence: 99%
“…The largest group are subjects not taking Cbl in their diets (strict vegetarians), those with Cbl malabsorption due to simple atrophic gastritis affecting at least 10% of the elderly and, in decreasing numbers, those who have undergone a gastrectomy. A reduced level of R-binder (TC-I and III) and a relatively low level of Cbl on TC-II, the significant Cbl transport protein, has been found in the elderly, although the significance of this is not clear (Marcus et al, 1987;Metz et al, 1996). These patients who do not consume enough Cbl or do not absorb it normally, have low Cbl stores but, presumably, are not, as yet, sufficiently Cbl-deficient to develop MA or neuropathy and most never do so.…”
Section: The Blood and Marrowmentioning
confidence: 99%
“…5 TC is responsible for transport of vitamin B 12 to the tissues. The vitamin B 12 associated with TC (holoTC) represents the functionally important fraction of plasma vitamin B 12 .…”
mentioning
confidence: 99%
“…Typically, vitamin B 12 deficiency is suspected only when an individual presents with hematologic manifestations of megaloblastic anemia, which occur only in the most severely vitamin B 12 -depleted individuals (5 ). Total plasma vitamin B 12 concentration is the current standard clinical screening test for vitamin B 12 deficiency.…”
mentioning
confidence: 99%
“…First, we examined healthy older subjects from the general population with normal plasma cobalamin concentrations, whereas the other two investigators examined hospitaliz ed older patients with normal plasma cobalamin concentrations. Second, the control group in the study by Marcus et al 6 was considerably younger (median age 34 years) than our middle-aged control group (median age 56Í5 years). The age of the young control group is not mentioned in the study by Metz et al 7 Third, there is a di¡erence in the method used to determine the plasma holotranscobalamin concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…6,7 Marcus et al 6 suggested that this was due to alterations in the structure of the binding site for cobalamin on transcobalamin. In 1988, Herzlich et al 8 suggested that low holotranscobalamin concentration is an early indicator of cobalamin de¢ciency.…”
Section: Original Articlementioning
confidence: 99%